Benign liver tumors in children-single centre experience - Gontumukkala, Chalapathi; Teja, Ravi; G., Rajeev Kumar; J., Veera Swamy (International Surgery Journal, 2017)
Background: To assess the incidence and management of benign liver tumors. Methods: Retrospective analysis of patients who were admitted with benign liver tumors in a Medical College Hospital in southern part of India during the period of 2006 to 2016 were analyzed. Results: We have treated a total of 10 cases of benign liver tumors during the period of 2006 to 2016. The mean age of presentation was 2.1 year. Seven of the ten cases were haemangiomas, two babies had mesenchymal hamartomas, one had focal nodular hyperplasia. Of the seven babies with haemangiomas, four had focal, two had diffuse involvement of liver, one baby had giant haemangioma. Three of the 4 babies with focal haemangiomas regressed during follow up, one baby lost follow up. One of the two babies with diffuse haemangioma developed high output cardiac failure but responded to digoxin, diuretics and steroids and now under follow up. The new born baby with giant haemangioma involving left lobe of liver also had high output heart failure which was refractory to medical therapy and required left lobectomy. Two babies had large mesenchymal hamartomas involving right lobe required surgical resection. One patient with focal nodular hyperplasia was managed conservatively. Mean follow up was 36 months. There were no deaths. Conclusions: Benign liver tumors are rare, most of them are haemangiomas. Only few of them require surgery. Large mesenchymal hamartomas can be promptly treated by resection with minimal mortality.